Space-sharing Strategy for Building Dynamic Container Yard Storage Considering Uncertainty on Number of Incoming Containers - Siti Nurminarsih; Ahmad Rusdiansyah; Maulin Masyito Putri (Jurnal Teknik Industri, 2017)
The implementation of AEC (Asian Economic Community) leads to demand increase at ports in Indonesia. This increasing demand is followed by operational efficiency at the port as well. In fact, ports in Indonesia have an average dwell time for 5 days. One of the causes of this long dwell time is container transfer inefficiencies during loading process. In this research, we will focus in yard management and increasing land utilization. To increase the land utilization, we develop the space-sharing concept to reduce the initial space needed for a given workload. Since the ships arrivals are also varying, this concept will be possible. We develop the concept by adding uncertainty on number of incoming containers at operational level as the determining factor in planning a shared yard area. We propose a simulation approach to evaluate strategies in making yard template.